Ajaran Misbruik Van Omstandigheden Sebagai Alasan Hakim dalam Memperbaiki Suatu Perjanjian (Analisis Putusan Pengadilan Negeri Palangka Raya Nomor 160/Pdt.G/2016/PN Plk) - Hayati, Mulida; Evi, Evi; Sudiarti, Elin (Universitas Ekasakti, 2024)
In the contract law that applies in Indonesia, an agreement can be canceled if the agreement is made through mistake, coercion and fraud. However, in the development of civil practice, it is also known that there is abuse of circumstances (misbruik van omstandigheden) as a reason for canceling an agreement. In the legal system in force in Indonesia, abuse of conditions in agreements (misbruik van omstandigheden) is a relatively new topic in the study of Indonesian civil law, both in theory and judicial practice. The court decision that is the study of the doctrine of abuse of circumstances in agreements is the case between Parluhutan Sirait and Benny Arifin as stated in the Palangka Raya District Court Number 160/Pdt.G/2016/PN Plk. From this decision it can be concluded that the agreement made by the parties must be balanced in terms of determining the rights and obligations given to the parties. Where debtors and creditors have an equal bargaining position. If an imbalance is found in the agreement, the judge can make his own judgment as to the basis for misuse of the conditions in the agreement. In this decision, the panel of judges had noticed indications of abuse of opportunity which became the basis for applying the doctrine of abuse of circumstances which was possible due to the imbalance and incompatibility of the positions of the parties involved in the agreement.